Modeling the hardening process of monolithic reinforced concrete structures in Elcut Pro software package. Issue 1 (November 2020) - Korobkov, S; Mikhailov, D; Gnyrya, A; Titov, M
Abstract: Modeling of heating a monolithic tape grillage using heating insulated wires in the ELCUT Pro 6.3 software and computing complex and the WinConcret add-on are discussed in the article. This type of concrete heating is used at a multi-storey residential complex "Alye Parusa" in Microdistrict "Severny", a rural settlement of the Tomsk region near the river. The initial parameters were introduced for the object under construction in Elcut Pro software package with the WinConcret add-in. As a result of the calculation, an analysis of the temperature fields in the section of a monolithic tape grillage was carried out, as well as graphs of the temperature dependence on time and graphs of the strength dependence on the heating time. It was found that when concrete was heated with the help of insulated heating wires, the thermal energy was distributed more evenly over the entire cross section of the grillage, which led to an increase in the entire structure strength.